Membangun Kesadaran Hukum Konsumen Muslim Terhadap Produk Berlabel Halal Di Era Masyarakat Ekonomi Asean - Triana Sofiani (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This paper is the result of research with located in the city of Pekalongan, which aims to explore legal awareness and efforts to build awareness of Muslim consumers against halal labeled products. The research method are empirical juridical, with qualitative approach. The data collection technique using observation, interviews and literary studies. Techniques to check the validity of data, using triangulation and analysis using an interactive model. The result of research shows that, the law awarness of Muslim consumer , for middle-lower Muslim consumer, the level of law awareness are still at the level of knowledge. But for middle-upper Muslim consumers, have knowledge and understanding about law and policy of halal product, so their attitude and behavior when buying or consuming a product have considered the there or no of halal labels listed in the product, even knowing about the validity of halal certification of the products which will be purchased and consumed. Factors that affect the Muslim consumer's law awareness of halal products, among others: education, economics, religion (religiosity) and social culture. Efforts to build law awareness of Muslim consumer are through education, for example with socialization and campaign about halal products and legal foundations, so as to create a consumer society are smart and conscious of halal, to confront of MEA era.